Tanah Adalah “Rahim” Perempuan Papua - Stefanus Mahuze (P3TK, Sanata Dharma University, 2022)
AbstractPapua experienced turmoil almost every year and often becomes an interesting subject for public discourse. However, Papuans are powerless when it comes to determining their own future. For sixty years (1962-2022), Papuans have to survive amidst the smell of bloodshed and the sounds of gunshots, demonstrations, lamentations, and other commotions that hinder human development. These have invited various parties to gather and think for solutions for peace. Despite this, the ideology of “NKRI Harga Mati” (Non-negotiable Sovereignty of the Unitary State of the Republic of Indonesia) has gained more popularity than the humane concept of Pancasila. The conflict driven by populist ideology has created scars in the history of the indigenous people of Papua, especially for Papuan women. The 117 years (1905-2022) of the Gospel preached in Papua has not been sufficient to liberate the Papuans. The patriarchy that preaches justice and humanity is likened to a fashion show for false generosity. They cry out for justice and yet they oppress Papuan women. This experience calls for a theological reflection from the lives of Papuan women. In using Delores S. William’s womanist theological framework, the author will discover how God speaks in the history of Papuan women and how God acts through their being.AbstraksiPapua selalu mengalami gejolak hampir enam puluh tahun (1962-2022), di mana orang Papua harus bertahan hidup di tengah bau pertumpahan darah dan suara tembakan, demonstrasi, ratapan, dan keributan lainnya yang menghambat pembangunan manusia. Situasi ini tidak pernah diselesaikan dengan cara yang benar tetapi melalui pendekatan yang justru menimbulkan masalah baru seperti penggundulan hutan yang berujung pada tindakan kekerasan dan diskriminasi terhadap perempuan Papua. Hal ini menunjukkan betapa kuatnya patriarki mendominasi penyelesaian konflik di Papua. Mereka selalu mengkhotbahkan keadilan dan kemanusiaan disamakan dengan “pertunjukan busana” untuk kedermawanan palsu. Pengalaman ini membutuhkan refleksi teologis baru dari kehidupan perempuan Papua dengan menggunakan perspektif Delores S. Williams tentang teologi kewanitaan. Dari kerangka teologis Williams, kita akan menemukan bagaimana Tuhan berbicara dalam sejarah perempuan Papua dan bagaimana Tuhan bertindak melalui keberadaan mereka.